Planetary Atmospheres and Urban Society After Fukushima - Thouny, Christophe; Yoshimoto, Mitsuhiro (Springer Singapore : Imprint: Palgrave Macmillan, 2017)
This collection examines the events of Fukushima in Japan in terms of urban sociology and cultural politics, both as a planetary event and a dual economic and environmental crisis which indelibly marked Japan and the wider global community. It considers what cultural forms can express this situation, problematizing the national frame of analysis in terms of the concept of the planetary. Building on recent debates in ecocriticism and debating the spatial logic of containment that reduces the event of Fukushima to a place-bound object argues for a close-reading of cultural texts and local urban practices in Fukushima Japan to articulate different narratives of the planetary and redefine our topologies of attachment to local places beside national discourses of unity, resilience and global strategies of risk management, opening the way to a rethink of Japan's cultural politics of Japan after March 2011. .